2021
DOI: 10.7554/elife.67781
|View full text |Cite
|
Sign up to set email alerts
|

An adhesion G protein-coupled receptor is required in cartilaginous and dense connective tissues to maintain spine alignment

Abstract: Adolescent idiopathic scoliosis (AIS) is the most common spine disorder affecting children worldwide, yet little is known about the pathogenesis of this disorder. Here, we demonstrate that genetic regulation of structural components of the axial skeleton, the intervertebral discs, and dense connective tissues (i.e., ligaments and tendons) are essential for the maintenance of spinal alignment. We show that the adhesion G protein-coupled receptor ADGRG6, previously implicated in human AIS association studies, is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…Similarly, a common variant (rs1891308) near ADGRG6 , a G protein-coupled receptor, is associated with increased torso length. Mice with conditional knockouts in ADGRG6 have spine abnormalities and spine alignments directly correlated with reduced torso length ( 52 ). Thus, GWAS of skeletal proportions pinpoints genes previously associated with skeletal developmental biology and Mendelian skeletal phenotypes and identifies candidates for future functional and knockout studies.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a common variant (rs1891308) near ADGRG6 , a G protein-coupled receptor, is associated with increased torso length. Mice with conditional knockouts in ADGRG6 have spine abnormalities and spine alignments directly correlated with reduced torso length ( 52 ). Thus, GWAS of skeletal proportions pinpoints genes previously associated with skeletal developmental biology and Mendelian skeletal phenotypes and identifies candidates for future functional and knockout studies.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a common variant (rs1891308) near ADGRG6 , which encodes a G protein–coupled receptor, is associated with increased torso length. Mice with conditional knockouts in ADGRG6 have spine abnormalities that reduce torso length ( 48 ). Thus, our GWAS of SPs identifies genes that were previously associated with skeletal developmental biology and Mendelian skeletal phenotypes, demonstrating the potential for future functional and knockout studies.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Gpr126 deficiency also leads to multiple defects in peripheral nerves [104], inner ear (in zebrafish) [105], placental development [106], and lack of myelination in the peripheral nervous system (PNS) [107]. More recent studies in cell typespecific Gpr126 knock out animals further indicated a role for GPR126 in the regulation of body length and bone mass as well as the maintenance of spinal alignment [108,109]. In line with these, GPR126 mutations and/or genetic variants in humans are associated with several disorders, including adolescent idiopathic scoliosis [110], arthrogryposis multiplex congenita [111], and intellectual disability [112].…”
Section: Adgrg6/gpr126mentioning
confidence: 99%